Metastability, resets and large deviations in open quantum systems - Rose, Dominic C. (2019)
In this thesis we apply, and build upon, a comprehensive theory of metastability in open quantum systems. We gain a full understanding of the long time states and the dynamics between them in a 1D open quantum Ising model, and a glassy, dissipative quantum East model: in order to do this, we develop algorithmic approaches to conducting such analyses in generic models exhibiting a metastability which can be considered classical. In addition, we provide an extensive discussion of the use of symmetries in the numerical study of open quantum systems, containing results of substantial use throughout this work. We finish with a general set of results about the spectra of operators describing the evolution of classical or quantum models undergoing stochastic resetting, allowing a precise analysis of the effect of resets on metastability in the 1D open quantum Ising model.